“A Study To Assess The Effectiveness Of An Information Booklet On Awareness Regarding Computer Vision Syndrome Among Bca Students In A Selected Metropolitan College” - Mrs. Greeshma Minesh; Ms. Neswari James Fernando; Ms.Sukanya Jangade; Ms. Mansi Pravin Chavan (Revista Electronica de Veterinaria, 2024)
Computer vision syndrome, also referred to as digital eye strain, describes a group of eye and vision related problems that results from prolonged computer, tablet, e-reader and cell phone use. Many individuals experience eye discomfort and vision problems when viewing digital screen for extended periods. The study to aims to assess the knowledge regarding computer vision syndrome among second year BCA students in selected college of metropolitan city. A quantitative experimental approach one group pre-test, post-test design was used for this study which was conducted in selected college of metropolitan city. 30 sample was selected using non-probability convenient sampling technique. Pre-test was conducted by administering a structured interruptive questionnaire, with interpretive educative session on computer vision syndrome among second year BCA students was given on same day. Post-test was conducted on 7thday and data was analyzed using descriptive statistics to find, pre-test knowledge score on interpretation with selected baseline variables.Analysis and interpretation give description of the study. Result shows that the level of knowledge regarding computer vision syndrome after providing information booklet is increased. The knowledge mean score of BCA students in pre-test was 8.43 whereas post-test was 14.4 with t value obtained is 10.73. The study showed that maximum students had inadequate knowledge regarding computer vision syndrome, the knowledge on computer vision syndrome has improved after the administration of information booklet was an effective teaching strategy in improving the knowledge on computer vision syndrome.